Experimental investigation on thermal management of lithium-ion battery pack for formula student electric vehicle using air-cooling system - Sagar Wankhede; Ajay D. Pingale; Atharva Kale (Energy Storage and Saving, 2025)
The increasing adoption of electric vehicles (EVs) has driven extensive research and development efforts to optimize the performance and safety of their energy-storage systems, particularly lithium-ion battery (LIB) packs. Elevated temperatures in EV batteries primarily result from thermal instability during various operating, traveling, and charging conditions. In formula student electric vehicle (FSEV) competitions, where efficiency and reliability are critical, effective cooling of the battery pack (BP) is essential. This study analyzed the cooling performance of an air-cooled thermal management system using relevant system parameters and precise thermal modeling through CFD simulations. Various cooling parameters, such as coolant flow rate, fan speed, and cooling channel geometry, were systematically adjusted to evaluate their effects on BP temperature distribution, thermal equilibrium, and overall performance. Key metrics, including maximum temperature and temperature distribution within the battery module, were used to compare simulation results and optimize outcomes for future applications. Experiments validated the simulations of the optimal solution. The results of this investigation provide valuable insights for designing and improving active cooling systems for LIBPs in FSEVs. The average variance of the obtained temperature data was 4.256% based on simulation results. At an air velocity of 17 m·s−1, the BP temperature remained within the ideal range of 30–40 °C. Enhanced cooling strategies can improve the thermal stability of bBPs, extend their lifespan, and reduce the risk of thermal runaway.